Optimal control of an age-structured problem modelling mosquito plasticity - Li, Lin Lin; Ferreira, Cláudia Pio [UNESP]; Ainseba, Bedreddine (Elsevier, 2019)
In this paper, we study an age-structured model which has strong biological background about mosquito plasticity. Firstly, we prove the existence of solutions and the comparison principle for a generalized system. Then, we prove the existence of the optimal control for the best harvesting. Finally, we establish necessary optimality conditions.
Keywords: Biological modelling; Optimal control; Optimality conditions